If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1x + -1x + 5 = 12 + 3 Reorder the terms: 6 + 5 + -1x + -1x = 12 + 3 Combine like terms: 6 + 5 = 11 11 + -1x + -1x = 12 + 3 Combine like terms: -1x + -1x = -2x 11 + -2x = 12 + 3 Combine like terms: 12 + 3 = 15 11 + -2x = 15 Solving 11 + -2x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2x = 15 + -11 Combine like terms: 11 + -11 = 0 0 + -2x = 15 + -11 -2x = 15 + -11 Combine like terms: 15 + -11 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| 12m-15=21 | | 1/4(3x+8)=16 | | 3y/(10y-30)+5y/(6y-18) | | 60=-22+a | | 7/8-(-1/10)+(-3/5)= | | 4.25-7.06= | | -7/10+(-5/12)-(1/4)= | | -100+j=345 | | -19=-4+g | | 2/3(9-6)+40= | | 8x^2-8/x/8(x^2+8)/26x^2-31x | | 6y/y-10=9y/y-10 | | 4x+9+8x+3=180 | | z/-7=23 | | -12+3f=3 | | 1.42y=3.16(y-8.57) | | x+(-5)=-8 | | (g+6)=-20 | | 5x^2-5x+10=x^2+10x | | 5w+7=2w+7 | | 714/9 | | 29=40+p | | 7=3b+13 | | 22=d+(1/4) | | Z+-14=-5 | | 3x-8+5x+10=90 | | -3n=6(9-n) | | 2x+5.34=5.39 | | (9/7)(5) | | 11y-12y=0 | | 5/6x-17=-7 | | 4b+(1/2)=(1/2) |